Multisite Dopamine Sensing With Femtomolar Resolution Using a CMOS Enabled Aptasensor Chip - Sessi, Violetta; Ibarlucea, Bergoi; Seichepine, Florent; Klinghammer, Stephanie; Ibrahim, Imad; Heinzig, André; Szabo, Nadine; Mikolajick, Thomas; Hierlemann, Andreas; Frey, Urs; Weber, Walter M.; Baraban, Larysa; et al. (Frontiers in Neuroscience, 2022)
Many biomarkers including neurotransmitters are found in external body fluids, such as sweat or saliva, but at lower titration levels than they are present in blood. Efficient detection of such biomarkers thus requires, on the one hand, to use techniques offering high sensitivity, and, on the other hand, to use a miniaturized format to carry out diagnostics in a minimally invasive way. Here, we present the hybrid integration of bottom-up silicon-nanowire Schottky-junction FETs (SiNW SJ-FETs) with complementary-metal–oxide–semiconductor (CMOS) readout and amplification electronics to establish a robust biosensing platform with 32 x 32 aptasensor measurement sites at a 100 µm pitch. The applied hetero-junctions yield a selective biomolecular detection down to femtomolar concentrations. Selective and multi-site detection of dopamine is demonstrated at an outstanding sensitivity of ~ 1 V/fM. The integrated platform offers great potential for detecting biomarkers at high dilution levels and could be applied, for example, to diagnosing neurodegenerative diseases or monitoring therapy progress based on patient samples, such as tear liquid, saliva, or eccrine sweat.